The mechanism underlying metastasis in triple-negative breast cancer: focusing on the interplay between ferroptosis, epithelial-mesenchymal transition, and non-coding RNAs - Chen, Ziyi; Zhao, Yi (Frontiers in Pharmacology, 2025)
Triple-negative breast cancer (TNBC) is a type of breast cancer with lack the expression of estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2). It is the most aggressive breast cancer and the most difficult to treat due to its poor response to treatments and extremely invasive characteristics. The typical treatment for TNBC frequently results in relapse because of the lack of particular treatment choices. It is urgent to focus on identifying a workable and effective target for the treatment of TNBC. Cancer metastasis is significantly influenced by epithelial-mesenchymal transition (EMT). Ferroptosis is an iron-dependent cell death form, and changes its key factor to affect the proliferation and metastasis of TNBC. Several reports have established associations between EMT and ferroptosis in TNBC metastasis. Furthermore, non-coding RNA (ncRNA), which has been previously described, can also control cancer cell death and metastasis. Thus, in this review, we summarize the correlation and pathways among the ferroptosis, EMT, and ncRNAs in TNBC metastasis. Also, aim to find out a novel strategy for TNBC treatment through the ncRNA-ferroptosis-EMT axis.